Knowledge sharing activities among public sector employees: Evidence from Indonesia - Supriatna, Metha Djuwita (University of Islam Malang, 2020)
Knowledge sharing has an important role in the management of any organization. It can lead to increased knowledge creation, collaboration level, and level of innovation, which, in turn, increases organizational performances. However, few studies have empirically examined the effect of knowledge sharing activities on an individual's belief in a public sector organizational setting, especially in Indonesia. This study was conducted to analyze the role of knowledge sharing in affecting the activities of creative self-efficacy within public organizations. This study used purposive sampling which designed to focus on employees who have positioned as a researcher in one of Directorate of Ministry of Public Works and Housing of the Republic of Indonesia. The questionnaire used in this study was adapted from Brockhus and Yu instruments. The result of this study shows that there is a positive and significant effect of knowledge sharing activities on creative self-efficacy. The higher the level of knowledge sharing activities within the organization, the more it will encourage creative self-efficacy. The majority of the respondent in this study that classified as Y generation (Millenials) was the main reason of the differences between the conclusion of this study and previous ones who argues that knowledge sharing initiatives are more difficult to be implemented in public sector organization as many of public sector officers believe that the activities of knowledge sharing meant losing power and an extra work surface.